2020
DOI: 10.1136/ebmental-2019-300130
|View full text |Cite
|
Sign up to set email alerts
|

Mental health disorders research in Europe, 2001–2018

Abstract: BackgroundThe burden of mental health disorders in Europe is well above the world average and has increased from 11.5% to 13.9% of the total disease burden in 2000 and 2015. That from dementia has increased rapidly, and overtaken that from depression as the leading component. There have been no analyses of the research activity in Europe to combat this burden.MethodologyWe identified research papers in the Web of Science (WoS) with a complex mental health disorders filter based on title words and journal names… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…However, we excluded those whose cause is primarily genetic ("Autism and Asperger syndrome", "Childhood behavioural disorders", and "Idiopathic intellectual disability"). [This was the definition adopted for a recent project to map five European non-communicable disease research outputs in 2002-13 for the European Union [15,16]. It was intended to exclude those mental health disorders that are not readily treatable as a result of research.]…”
Section: The Burden Of Mental Health Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we excluded those whose cause is primarily genetic ("Autism and Asperger syndrome", "Childhood behavioural disorders", and "Idiopathic intellectual disability"). [This was the definition adopted for a recent project to map five European non-communicable disease research outputs in 2002-13 for the European Union [15,16]. It was intended to exclude those mental health disorders that are not readily treatable as a result of research.]…”
Section: The Burden Of Mental Health Disordersmentioning
confidence: 99%
“…Drug treatment (DRUG) is by far the most popular type of research and is actively supported in Egypt (EG) and Iran (IR). The latter, and Turkey (TR), are also active in non-pharmaceutical treatments (TREA), whereas research on these is almost ignored in most of the other OIC countries, and the combined OIC output is only 3.7% of the total compared with 5.8% in Europe [16]. Epidemiology (EPID) is researched fairly equally in all the countries listed here, but five of them do noticeably more than expected (Indonesia, ID; Lebanon, LB; Uganda, UG; Tunisia, TN and Malaysia, MY).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety disorders (ADs) are some of the most prevalent mental health disorders, twice as common in women than men. 1 2 They affect 61.5 million people in Europe, 3 and findings from a recent prevalence study in Spain indicated that about 11% of adults are affected by an AD. 4 ADs have an important negative impact on the health-related quality of life of patients as well as in their economies, due mostly to indirect costs.…”
Section: Introductionmentioning
confidence: 99%
“…Stein et al 2017). Afectan a más de 260 millones de personas (Organización Mundial de la Salud, 2017) y aproximadamente a 61.5 millones de adultos en Europa (Begum et al 2020), mientras que en España, un estudio reciente indica que afectan al 11% de personas (Villagrasa et al 2019). Los TA son los más frecuentes dentro del ámbito de Atención Primaria (AP) y concretamente, el trastorno de ansiedad generalizada (TAG) tiene una alta prevalencia (Alonso and Lépine 2007;Bados 2017).…”
Section: Introductionunclassified